1991
DOI: 10.1002/mrd.1080280413
|View full text |Cite
|
Sign up to set email alerts
|

Artificial activation of porcine oocytes matured in vitro

Abstract: These studies were undertaken to understand the biological basis of artificially induced activation of meiotic metaphase II oocytes and to develop a source of oocytes as recipients for cloning by nuclear transfer. In vitro matured porcine oocytes were pulsed with various voltages of electricity and evaluated for pronuclear formation. The percentage of eggs that activated was significantly greater for the higher voltages. The effect on activation of the temperature of the ovaries returning from the abattoir was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 14 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…Application of one or more electric pulses has been s h o w n t o i n d u c e m e i o t i c r e s u m p t i o n a n d pronuclear formation in mouse [123,129], rabbit [8,124], sheep [130], cattle [6,131], pig [125,126,[132][133][134] and marmoset [135] oocytes. Furthermore, electrically activated rabbit [8], cattle [6] and pig [126,132,133,[136][137][138] oocytes undergo cleavage and parthenogenetic development to the blastocyst stage.…”
Section: Calcium Ionsmentioning
confidence: 99%
“…Application of one or more electric pulses has been s h o w n t o i n d u c e m e i o t i c r e s u m p t i o n a n d pronuclear formation in mouse [123,129], rabbit [8,124], sheep [130], cattle [6,131], pig [125,126,[132][133][134] and marmoset [135] oocytes. Furthermore, electrically activated rabbit [8], cattle [6] and pig [126,132,133,[136][137][138] oocytes undergo cleavage and parthenogenetic development to the blastocyst stage.…”
Section: Calcium Ionsmentioning
confidence: 99%
“…This ability allows different manipulations with the zygote such as the creation of parthenogenetic (monoparental) embryos, and nuclear/pronuclear transfer, including interspecies transfer (Chang et al, 2003;Hammer et al, 2001;Liu et al, 2004b;McGrath and Solter, 1983;McGrath and Solter, 1984;McGrath and Solter, 1986). The mature oocyte, awaiting the fertilization at metaphase II, gets activated by the penetrating sperm, but it also can be artificially activated in vitro by chemicals, or even by temperature and pH shifts (Meo et al, 2004;Nagai, 1987;Prather et al, 1991). After activation or fertilization, the oocyte completes meiosis II and one set of maternal chromosomes is extruded as second polar body.…”
Section: Introductionmentioning
confidence: 99%
“…The sperm activation stimulus can be simulated artificially, ie parthenogenetically, via, for example by Ca 2+ ionophore A23187 (Ware et al, 1989), protein synthesis inhibitors (First et al, 1992) or ethanol (Nagai, 1987) and also by an electric pulse. It has been demonstrated that electrically activated oocytes exhibit similar characteristics to penetrated eggs: establishment of zona pellucida block prevents polyspermic penetration (Gwatkin et al, 1973;Behalova et al, 1992), completion of meiosis, chromatin decondensation and pronuclear formation (Landa and Hdjkovd, 1989;Prochazka et al, 1992), cleavage (Tarkowski et al, 1970;Kaufman et al, 1975; Prather et al, 1991;Prochazka et al, 1993) and in particular cases limited postimplantation development (Ozil, 1990). Although the kinetics of pronucleus formation in activated bovine oocytes has been monitored (Landa and Hajkova, 1989;Powell and Barnes, 1992) (Xu et al, 1986).…”
Section: Introductionmentioning
confidence: 99%